2012
DOI: 10.1097/iae.0b013e3182561f7c
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Rhegmatogenous Retinal Detachment Associated With Choroidal Detachment in Chinese Using Ubm

Abstract: Retinal detachment associated with CD occurs more frequently in older people or in patients with high myopia, who usually present with low intraocular pressure and multiple retinal breaks. UBM examination can reduce false-negative rate of RRDCD, determine CD degree quantitatively, and guide classification and treatment. UBM combined with B ultrasound testing can provide a precise diagnosis of rhegmatogenous retinal detachment degree and may have important clinical significance for preoperative diagnosis of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 4 publications
0
57
0
Order By: Relevance
“…13 The choroidal detachment was classified by using UBM. 10 Vitreous incarceration was defined as moderate/high reflective membrane like-echoes extending from and continuous with the peripheral vitreous gel into the sclerotomy. 13 Statistical analyses were performed by SPSS, using t test and W 2 test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The choroidal detachment was classified by using UBM. 10 Vitreous incarceration was defined as moderate/high reflective membrane like-echoes extending from and continuous with the peripheral vitreous gel into the sclerotomy. 13 Statistical analyses were performed by SPSS, using t test and W 2 test.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study proved UBM examination could reduce the false-negative rate of retinal detachment associated with choroidal detachment (CD) and determine the degree of CD quantitatively. 10 To gain further insight into the differences between clinical features in 20G and 23G, we performed this prospective study using UBM to investigate sclerotomy sites and the pars plana region in vivo before and after 20G and 23G vitrectomy.…”
mentioning
confidence: 99%
“…Clinical symptoms of RRDCD include severe uveitis, ocular hypotony, deep anterior chamber, concentric folding, and iridophakodonesis [1,2,3]. RRDCD progresses rapidly and has a poor prognosis because it quickly proceeds to severe proliferative vitreoretinopathy (PVR).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a large prospective study of RRD/CD patients has shown that a higher preoperative IOP and a smaller CD are significantly associated with a higher success rate in RRD/CD repair surgery (Li et al. ). In addition, the current study also demonstrated that subtenon TA is superior to systemic Dex in term of less interference of patient's physiological steroid balance and in term of postoperative macular recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study was designed to evaluate the effect of a subtenon injection of TA on RRD/CD patients as compared to the effects from conventional systemic steroid administration, with the major outcome measures of the changes in preoperative CD and intraocular pressure (IOP) which have been indicated as risk factors for surgical repair failure (Li et al. ). In addition, drug concentration in the vitreous and plasma and the post‐operative rate of macular oedema were also evaluated.…”
Section: Introductionmentioning
confidence: 99%